Foreign language anxiety, enjoyment, and boredom among Chinese secondary students: a control-value theory approach - Zhiyuan Li; Li Xing (Humanities & Social Sciences Communications, 2024)
Abstract For decades, studies on learner emotions in foreign language learning have been predominantly focused on foreign language anxiety, and recent years have witnessed a surge in the exploration of other positive and negative emotions such as enjoyment and boredom. The current study aimed to extend this line of inquiry and explored the bidirectional relations between foreign language achievements and learner emotions through a questionnaire study among English learners (n = 756) in Chinese senior secondary schools, an understudied population in foreign language emotion research. Results indicated that the three emotions were significantly related to each other. Further analyses suggested that anxiety and boredom were significant predictors of achievements, and that language achievements predicated all the three emotions. The study confirms the reciprocal relationships between language achievements and emotions and provides pedagogical implications for language teaching.